The performance of a sumerian wedding song (CT 58, 12) 13 - Mirelman, Sam (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2010)
A close examination of the Old Babylonian Sumerian song CT 58, 12, in terms of its graphic arrangement and its literary patterns, leads to a better understanding of its performance: male and female singers participate, soloists and choir alternate, and vocables feature prominently besides the Sumerian text. The song can be situated within the marriage ceremony.